Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.5 Exercises: 31



Work Step by Step

$\dfrac{d}{dx}((x^2+y^2)^2)=\dfrac{d}{dx}(4x^2y)\rightarrow$ Using the Chain Rule with $u=x^2+y^2\rightarrow\dfrac{du}{dx}=2x+\dfrac{dy}{dx}(2y)\rightarrow$ $\dfrac{d}{dx}((x^2+y^2)^2)=2(x^2+y^2)(2x+\dfrac{dy}{dx}(2y)).$ $2(x^2+y^2)(2x+\dfrac{dy}{dx}(2y))=\dfrac{dy}{dx}(4x^2)+8xy\rightarrow$ $\dfrac{dy}{dx}(x^2-x^2y-y^3)=xy^2-2xy+x^3\rightarrow$ $\dfrac{dy}{dx}=\dfrac{xy^2-2xy+x^3}{x^2-x^2y-y^3}.$ At $(1, 1)\rightarrow\dfrac{dy}{dx}=\dfrac{(1)(1^2)-2(1)(1)+(1)^3}{1^2-(1^2)(1)-1^3}=0.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.